Service Management Systems and MS ISO based products : a reflection. - Hamzah, Mohd Sahandri Gani; Abdullah, Saifuddin Kumar (EuroJournals, 2009)
The MS ISO system is working towards creating a culture of an environment of teamwork by following principles, rules and etiquettes which stresses on the quality of process and products services. The quality excellence of the organization service processes are monitored by an Internal Audit mechanism, which is simultaneously integrated with coaching activities during document examinations to maintain service process and product excellence. This reflection has become a part of the quality evaluation system to ensure work processes which are more sensitive to the improvement effort which focuses on efficiency, punctuality and costs effectiveness.